Characteristics of Electromagnetic Coupling with A Wire through Shielding Enclosure - Yanpeng Sun; Liwei Sun; Xiaohe An (Institute of Advanced Engineering and Science, 2014)
The paper presents a numerical method based on Finite Difference Time Domain (FDTD) in both frequency and time domain for modeling the coupling of an incident electromagnetic pulse(EMP) with a conducting wire through a metallic shielding enclosure with a small aperture. Simulation and analysis are done by radius, length, and number of the wires, the incidence angle of EMP and the polaration angle of electric field in consideration. The simulation result shows that interference of the electromagnetic coupling into the shielding enclosure can be affected in different degrees by above factors. At low frequency, the larger the leakage length, the radius or the number of the wire penetrated into the cavity, the more interference is coupled into the shielding cavity from electromagnetic field. Also, the smaller the incident direction angle of propagation of the electromagnetic pulse or the polarization direction angle of the incident electric field, the more easily the electromagnetic interference is coupled into the cavity. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3984